The double question of the foundation and the principle of identity in F. W. J. Schelling’s «Erlangen Lectures» - Miguel Ángel Ramírez Cordón (Pensamiento. Revista de Investigación e Información Filosófica, 2019)
Based on the Lessons of Erlangen, it is going to be analyzed what is the procedure by which is built on Schelling’s philosophy the concept of freedom. Freedom which, according to the Freiheitsschrift, is the capacity to choose between good and evil, it is not in deed, but the process by which the foundation of science and the principle of identity are divided. The division is not however a rift that marks the independence between the two terms but, on the contrary, foundation and identity have a relationship of antecedent and consequent respectively, they occupy two tasks, two different competences, and whose whole job is only the final fruit of freedom.